2011
DOI: 10.1590/s0101-28002011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Controle da hiperfosfatemia na DRC

Abstract: A taxa de filtração glomerular é o principal indicador de função renal em indivíduos saudáveis e doentes. Apesar de todo o desenvolvimento da medicina em nossos dias, ainda há dificuldade para definir-se essa taxa com precisão na prática diária. Marcadores precoces de lesão renal são importantes, porque a taxa de filtração glomerular se reduz antes do aparecimento dos sintomas ou sinais de insuficiência renal. A cistatina C tem sido apontada como uma alternativa, mas ainda não foi testada em muitas condições. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
3
0
1
Order By: Relevance
“…The consumption of phosphorus was consistent with recommended levels 3 , and can contribute towards increases in the serum levels of this mineral, which were also found to be appropriate. Furthermore, the majority of foods in this group have a relationship between phosphorus and protein that is higher 23 . For these reasons, it is rare for individuals undergoing hemodialysis to comply with this recommendation, which would require adjustments that take into account the particularities of this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption of phosphorus was consistent with recommended levels 3 , and can contribute towards increases in the serum levels of this mineral, which were also found to be appropriate. Furthermore, the majority of foods in this group have a relationship between phosphorus and protein that is higher 23 . For these reasons, it is rare for individuals undergoing hemodialysis to comply with this recommendation, which would require adjustments that take into account the particularities of this population.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it is rare for individuals undergoing hemodialysis to comply with this recommendation, which would require adjustments that take into account the particularities of this population. The low levels of consumption of these foods might have contributed towards the increased prevalence of inadequate levels of retinol and may explain the reduced average intake of calcium that was found, something which should not give rise to concern, since part of the calcium that comes from some of the chelations of phosphorus is absorbed and should be considered as a non-dietary source of this mineral 3,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning dietary data, (dietary record and food frequency table) in this study showed that the average consumption of milk and dairy products was found to be lower than the levels recommended for a healthy diet. The low levels of consumption of these foods might have contributed towards the increased prevalence of inadequate levels of retinol and may explain the reduced average intake of calcium that was found, something which should not give rise to concern, since part of the calcium that comes from some of the creations of phosphorus is absorbed and should be considered as a non-dietary source of this mineral (Fouque& Vennegoor 2007; Carvalho & Cuppari et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Diante do exposto, o EGFET formado por dispositivo EIS, composto de óxido de alumínio e eletrodo de referência contendo membrana seletiva [217], [220], [221], mostrou-se muito promissor para a aplicação inédita que propôs o trabalho de pesquisa, que foi medir a concentração de fosfato no DTF em tempo real, e com a contribuição de quantificar a massa de fósforo que é removida do paciente renal crônico nas sessões de hemodiálise. Trouxe também uma contribuição significativa no que diz respeito ao controle do nível de concentração de fósforo em pacientes renais crônicos, pois de acordo com trabalhos relacionados na literatura [32], [35], [222], [223], mostram a relevância do controle do nível de concentração de fósforo nos pacientes renais crônicos. Geralmente essa concentração nos pacientes em diálise os valores devem estar entre de 2,7 e 5,5 mg/dL [27], [28], e os valores das concentrações de fosfato no DTF utilizados nas medidas foram entre 0,4 e 7 mg/dL.…”
Section: Medidas Da Concentração De Fosfato No Dtfunclassified